2015
DOI: 10.1111/bph.13109
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 mimetic peptide controls the inflammatory and fibrotic effects of silica particles in mice

Abstract: BACKGROUND AND PURPOSEEndogenous glucocorticoids are pro-resolving mediators, an example of which is the endogenous glucocorticoid-regulated protein annexin A1 (ANXA1). Because silicosis is an occupational lung disease characterized by unabated inflammation and fibrosis, in this study we tested the therapeutic properties of the N-terminal ANXA1-derived peptide annexin 1-(2-26) (Ac2-26) on experimental silicosis. EXPERIMENTAL APPROACHSwiss-Webster mice were administered silica particles intranasally and were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 51 publications
7
60
1
Order By: Relevance
“…As mentioned before, several studies have reported a correlation between the absence of AnxA1 and tissue damage and dysfunction in different models of disease, such as gout and lung fibrosis . In agreement with that, in the context of pneumococcal pneumonia, AnxA1 KO mice presented a reduction of lung compliance and FEV 100 , alterations that were also observed in patients affected by pneumococcal pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned before, several studies have reported a correlation between the absence of AnxA1 and tissue damage and dysfunction in different models of disease, such as gout and lung fibrosis . In agreement with that, in the context of pneumococcal pneumonia, AnxA1 KO mice presented a reduction of lung compliance and FEV 100 , alterations that were also observed in patients affected by pneumococcal pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this ligand–receptor interaction may represent a novel therapeutic target to inhibit fibrosis in chronic kidney disease (Neymeyer et al , 2015). The ANXA1 mimetic peptide Ac2-26 also has beneficial effects on lung function and pathology in mice with silicosis suggesting that it could be used as a therapeutic agent in lung disease (Trentin et al , 2015). …”
Section: Externalization Of Annexin A1 - and What Next?mentioning
confidence: 99%
“…24 These pro-resolving mediators act at different phases of the inflammatory response and are involved in blockade of leukocyte recruitment, inhibition of cytokine release, promotion of apoptosis, stimulation of phagocytosis, and decreasing vascular permeability. 3,4 Effectors of resolution ensure that these responses remain localized within the inflamed tissue and are extinguished within an adequate timeline. Of relevance, both AnxA1/AnxA1 Ac2–26 , and LXA 4 /ATL mediate their effects through a common G protein-coupled receptor: the formyl peptide receptor 2 (Fpr2/3), also called lipoxin A 4 receptor (ALX).…”
Section: Introductionmentioning
confidence: 99%